An Analysis of Illocutionary Acts Found in Joe Biden’s Victory Speech as a President - Diah Nawang Wulan; Yulianto (DISCOVERY JOURNAL, 2022)
In this research the researcher discussed the Illocutionary Acts in the utterances of Joe Biden's Victory Speech as a President. The aim of this research is to find out the types of Illocutionary Acts and Identify the context in Joe Biden's Victory Speech as a President. The researcher uses qualitative descriptive analysis method. The researcher collects the data from the script, then classification of the types and describes contexts of Illocutionary Acts. Based on the theories, the data analyzed one by one based on the utterances to know the types and context of illocutionary acts used. In this research, the researcher analyzed fifty one data. From the analysis, the researcher found four types of Illocutionary Acts used by Joe Biden in his victory speech as a president. They are Representative (admitting, announcing, asserting, notifying, proposing, stating, and telling), Commisive (pledging, promising, and wishing), Expressive (apologizing, greeting, thanking, and praising), and Declarative (declaring).